2014
DOI: 10.1161/strokeaha.114.004853
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Racial Disparity in Stroke Hospitalization and Economic Impact in Young Adults in the Buckle of Stroke Belt

Abstract: It is unclear whether recent stroke incidence and mortality rates in South Carolina have corresponded with national Background and Purpose-Mounting evidence points to a decline in stroke incidence. However, little is known about recent patterns of stroke hospitalization within the buckle of the stroke belt. This study aims to investigate the age-and race-specific secular trends in stroke hospitalization rates, inpatient stroke mortality rates, and related hospitalization charges during the past decade in South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…These findings indicate a racial disparity despite dramatic gains nationwide in stroke reduction. 9 Finally, a study of 162 stroke survivors revealed that AAs were less likely to report independence in overall functional performance at one year when compared with Whites, even after controlling for stroke severity. 10 Collectively, these findings provide strong evidence of racial differences in stroke recovery in South Carolina.…”
Section: Previous Research Related To Wissdom Focusmentioning
confidence: 99%
“…These findings indicate a racial disparity despite dramatic gains nationwide in stroke reduction. 9 Finally, a study of 162 stroke survivors revealed that AAs were less likely to report independence in overall functional performance at one year when compared with Whites, even after controlling for stroke severity. 10 Collectively, these findings provide strong evidence of racial differences in stroke recovery in South Carolina.…”
Section: Previous Research Related To Wissdom Focusmentioning
confidence: 99%
“…50,68,69 For example, 47% of blacks were estimated to have hypertension in 2015 compared with 40% of white non-Hispanics, consequently increasing their risk for stroke and heart failure. 1,[70][71][72] Studies of traumatic spinal cord injury and other chronic conditions suggest that blacks were more likely to receive informal care from other family members, friends, church support, and others, whereas whites were more likely to receive informal or family care from spouses. 73 Level of income was most directly related to the use of paid versus unpaid care.…”
Section: Special Concerns By Age Sex and Race/ Ethnicitymentioning
confidence: 99%
“…Differences in incidence, pathogenesis, and clinical outcome have long been noted when comparing IS among patients with different racial and ethnic backgrounds. Epidemiological studies highlight significant racial disparities with blacks having significantly higher stroke incidence compared to whites [6], younger age of incidence [7], and poorer functional outcomes [8]. …”
Section: Introductionmentioning
confidence: 99%